THE ROLE OF CONSERVATION IN PUBLIC HEALTH - Jobman, Erin (My University, 2017)
Abstract This is a report of my field experience (240 hours) completed at the Soltis Center and Monteverde Institutions in Costa Rica during the summer of 2015. Under the supervision of Dr. Raymond Tarpley, the director of the Conservet Program, the course explores concepts related to conservation and facilitates collaboration amongst veterinary students, veterinarians, biologists, and ecologists to identify levels of health dysfunction in the ecosystem and establish methods of intervention to protect public health. The Conservet Program included lecture-based discussions with local professionals about the biodiversity in Costa Rica, disease ecology, drivers of global health dysfunction, and conservation strategies. The course also provided opportunities for fieldwork data collection from two different eco-zones of rain forest and local farms to explore the complexity of environmental function. The fieldwork focused on birds, bats, rodents, local livestock, fish, and mosquitoes as sentinels for disease and ecosystem health. Diseases investigated include Dengue, Chikungunya, Chagas Disease, West Nile Virus, and Avian Influenza. With a focus on conservation, this program allowed me to develop a greater understanding of public health from studying the interface between human, animal, and environmental health. This report describes my field experience in Costa Rica and discusses the relevance of conservation efforts as it affects public health. The key to understanding emerging infectious diseases is to understand the protective effects of nature intact, and recognize the consequences of destroying it. This report will also discuss the MPH core competency courses and how they relate to my field experience.
Keywords: Costa Rican Ecology; Disease Investigation; Health Dysfunction